Implementasi Logika Fuzzy Mamdani dalam Menentukan Jumlah Pemesanan Produk pada PT Forisa Nusapersada Area Tarakan: Implementation of Mamdani's Fuzzy Logic in Determining the Number of Product Orders at PT Forisa Nusapersada Tarakan - Rita Tri Wulandari; Ummi Syafiqoh; M. Hafid (STMIK PPKIA Tarakanita Rahmawati, 2023)
PT Forisa Nusapersada, Tarakan is an industrial company engaged in the distribution and marketing of products. When ordering products from the head office, since the customer's product demand sometimes increases or decreases every month, it is sometimes necessary to repeat the order within a month, thus affecting the product inventory in the warehouse. This study applied Fuzzy Mamdani to determine the number of orders based on sales data, goods stock and incoming goods from March to August 2021. This method has 5 stages, fuzzy set formation, rule formation, implication function application, rule composition and defuzzification. The input variables were demand and supply, while the output was orders. The results showed that the determination of the value of the fuzzy set domain can affect the final results differently for each product variant. In this study, the value of the fuzzy set domain was from the minimum and maximum values of sales data, goods stock and incoming goods.